2020
DOI: 10.1177/2325967119892281
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Anterograde and Retrograde Lesser Trochanter Avulsion Repair

Abstract: Background: Lesser trochanter avulsions are rare injuries in adolescents. Severe cases with relevant fragment displacement can be treated surgically. However, no standard approach is available in the literature. Operative techniques are presently limited to anterograde fixations. A new retrograde approach to reduce operative difficulty and postoperative morbidity has been proposed. So far, no biomechanical comparison of these techniques is available.Hypothesis: Retrograde repair of the lesser trochanter with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Among pelvic and femoral avulsion fractures, the lesser trochanteric one is rarely encountered, representing from 1-2% [2,3] . They generally occur in adolescents, around 14 years, with ranges varying from 7 to 16 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among pelvic and femoral avulsion fractures, the lesser trochanteric one is rarely encountered, representing from 1-2% [2,3] . They generally occur in adolescents, around 14 years, with ranges varying from 7 to 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases in less than two years old children have been reported [6] . Male is largely more affected than female, representing 75% of patients [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selon la discipline et le mécanisme lésionnel, des apophyses différentes sont concernées : tubérosité ischiatique : course de haies, danse de ballet, gymnastique, sports de combat, ski nautique, football (flexion de hanche avec extension du genou) [5,33,39,43] ; EIAS : sprint, football, baseball [43] ; EIAI : football (shoot), sports de combat (coup de pied) [42] ; petit trochanter : sports de ballon [45] Physiopathologie…”
Section: Sports Prédisposantsunclassified
“…Complementary diagnostic imaging protocols are suggested in the form of MRI and CT scans ( Losco et al, 2019 ). Avulsion fractures are rarely suspected as a cause of groin pain ( Otto et al, 2020 ). Eberbach et al (2017) showed the frequency of various hip avulsion sites as follows: the anterior inferior iliac spine at 33.2%, ischial tuberosity at 29.7%, anterior superior iliac spine at 27.9%, iliac crest at 6.7%, lesser trochanter at 1.8%, and superior corner of the pubic symphysis at 1.2% of all cases.…”
Section: Avulsion Fracturesmentioning
confidence: 99%